Two-Phase Dechlorination/Detoxification of Lindane (Hexachlorocyclohexane). (29th September 2014) - Ghaffar, Abdul; Tabata, Masaaki; Mashiatullah, Azhar
Abstract : Dechlorination of lindane was carried out in a two-phase reaction. In first phase Devarda's alloy and sodium borohydride were used in aqueous/ethanol reaction media. The reaction duration and temperature were optimized. In first phase higher dechlorination (78%) was achieved at 80°C with 40-minute reaction time and the products were chlorobenzene, dichlorobenzene, and chlorocyclohexane. In second phase, Ca(OH)2 and sulfur were added in reaction media. The reactions conditions like temperature and reaction time were optimized. After 30 minutes, dechlorination was enhanced from 78% to 94% and the final products were benzene, phenol, catechol, benzenethiol, cyclohexane, cyclohexanol, and cyclohexanethiol. The results suggested that dechlorination of lindane in first and second phase was carried out through hydrodechlorination and substitution reactions, respectively. The developed method was applied for lindane containing real wastewater and higher dechlorination (91%) was achieved under optimized reaction conditions.